The value of cervical mediastinoscopy in the diagnosis of mediastinal lymphadenopathy - Akar, Erkan; Erkinuresin, Taskin (The European Research Journal, 2017)
Objective. This study retrospectively evaluated mediastinoscopic interventions performed for diagnostic purposes in cases with mediastinal lesions remained undiagnosed by other diagnostic methods. Methods. We retrospectively evaluated the medical information of 218 patientss that underwent diagnostic cervical mediastinoscopy for mediastinal lymphadenopathy apart from lung cancer staging between January 2011 and December 2015. The patients were evaluated for age, sex, distribution of sampled lymph node stations detected to have lymphadenopathy, intraoperative and postoperative mortality and morbidity, and histopathological diagnostic parameters. The gender-based distribution of the disease types diagnosed by cervical mediastinoscopy were analyzed with the Chi-Square test. Results. Two hundred and six (94.5%) of 218 patients were diagnosed by cervical mediastinoscopy. The most common diagnosis was sarcoidosis in women and bronchogenic carcinoma in men. Nineteen (8.7%) patients suffered minor complications, with pain being the most common; no major complication occurred. Conclusion. The present study shows that mediastinoscopy is still an invasive diagnostic method with high diagnostic accuracy that can be safely used with low rates of mortality and morbidity in a large proportion of patients with mediastinal lymphadenopathy of undetermined origin.